Long non-coding RNA H19 as a prognostic biomarker for oral squamous cell carcinoma - Kumar, Kiran; Hallikeri, Kaveri; Oli, Ajay Kumar; Radder, Kiran; Jain, Apoorva; Shilpasree, A. S.; Dhanapal, Raghu; Tabnjh, Abedelmalek Kalefh; Selvaraj, Siddharthan (Frontiers in Medicine, 2024)
Background: H19, a 2.3 kb lncRNA, has been linked to tumor metastasis and progression, but its significance in oral squamous cell carcinoma (OSCC) remains unclear. H19 was initially thought to have a tumor-suppressive function, but recent studies have shown it possesses both tumor-promoting and suppressive functions. The variation in H19 expression may be due to the influence of tobacco or low basal expression levels. However, there are limited studies available on the association between H19 and its role in the prognosis of OSCC. Objective: The present study analyzes the expression of H19 correlated to clinico-pathological parameters, tobacco habit, loco-regional recurrence, and overall survival. Method: A longitudinal study was undertaken using 96 formalin-fixed paraffin-embedded (FFPE) OSCC tissues and 30 FFPE adjacent normal mucosa (NM) tissues from patients who had surgery between 2015 and 2018. The tissues were subjected to quantitative reverse-transcription polymerase chain reaction (qRT-PCR) to determine H19 expression. The differential expression levels of H19 in OSCC were compared to clinicopathological variables and risk habits using the t-test and ANOVA. H19 expression correlated to overall survival was analysed by drawing Kaplan-Meier curve followed by the log-rank test. A multivariate Cox proportional hazards regression analysis was performed to determine ability of H19 to independently predict loco-regional recurrence and overall survival for OSCC. Result: H19 was significantly under expressed in OSCC compared to NM in both the study cases and the TCGA OSCC database. The lower expression of H19 was significantly associated with the tobacco smoking habit and was not associated with any clinical or pathological features. Multivariate Cox’s proportional hazards regression analysis indicated that low H19 expression and positive lymph node metastasis were independent predictors of overall survival for OSCC. Higher age, higher TNM staging, and low H19 expression were independent predictors of loco-regional recurrence. Conclusion: The findings in the present study indicate H19 is a novel prognostic marker and may provide a therapeutic strategy for the targeted treatment of OSCC, and tobacco may play a role in the expression of H19.